Implementasi Model Problem Based Learning Untuk Meningkatkan Kemampuan Pemecahan Masalah Dan Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam - UFN Marinih (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2020)
This study aims to determine the learning process of Islamic subject by using a problem based learning model, knowing the problem solving abilities and learning outcomes of 6th grade students in Cirebon City Kebon Baru IV Elementary School in Islamic subject learning through a problem based learning model, and to determine improvement in problem solving skills and learning outcomes. This study uses research quasy experiments methods. The sample used was class State Elementary 6th School Kebon Baru IV as an experimental class amounting to 34 students on grade in State Elementary School Kebon Baru VII as a control class totaling 34 students. The instruments used were observation, tests, field notes, and documentation methods. The results of the study after the application of the problem based learning model showed that the average post-test value of students' problem solving abilities in the experimental class was 78.8235 and controls 51.9118. The results of the hypothesis test indicate that there is a difference in the increase in problem solving abilities, namely the experimental class gets a higher value than the control class. While student learning outcomes in Islamic subject lessons after the application of the problem based learning model in the experimental class experienced a significant increase. The calculation of Islamic subject learning outcomes before the application of the problem based learning model had an average of 10.1471 after the application of the problem based learning model had an increase in the average Islamic subject learning outcomes of 18,2059.Penelitian ini bertujuan untuk mengetahui mengetahui proses pembelajaran Pendidikan Agama Islam dengan mempergunakan model problem based learning, mengetahui kemampuan pemecahan masalah dan hasil belajar siswa kelas 6 di Sekolah Dasar Negeri (SDN) Kebon Baru IV Kota Cirebon dalam pembelajaran PAI melalui model problem based learning, dan untuk mengetahui peningkatan kemampuan pemecahan masalah dan hasil belajar. Penelitian ini menggunakan metode penelitian kuasi eksperimen. Sampel yang digunakan adalah kelas 6 SDN Kebon Baru IV sebagai kelas eksperimen berjumlah 34 siswa, dan kelas 6 SDN Kebon Baru VII sebagai kelas kontrol berjumlah 34 siswa. Instrumen yang digunakan berupa metode observasi, tes, catatan lapangan, dan dokumentasi. Hasil penelitian setelah penerapan model problem based learning menunjukkan bahwa nilai rata-rata post-test kemampuan pemecahan masalah siswa kelas eksperimen adalah 78,8235 dan kontrol 51,9118. Hasil uji hipotesis menunjukkan bahwa ada perbedaan peningkatan kemampuan pemecahan masalah, yaitu kelas eksperimen mendapatkan nilai yang lebih tinggi dibanding kelas kontrol. Sedangkan hasil belajar siswa dalam pelajaran Pendidikan Agama Islam setelah penerapan model problem based learning di kelas eksperimen mengalami peningkatan yang cukup signifikan. Perhitungan hasil belajar PAI sebelum penerapan model problem based learning memiliki rata-rata 10,1471 setelah penerapan model problem based learning mengalami peningkatan rata-rata hasil belajar Pendidikan Agama Islam yaitu 18,2059.